Wong's essentials of pediatric nursing - Wong, Donna L.; Hockenberry-Eaton, Marilyn ;Wilson, David;Winkelstein, Marilyn L.;Schwartz, Patricia (St. Louis, Missouri : Mosby Elsevier, 2001)
"The text utilizes a highly-readable writing style and encourages a whole-body approach beginning with child development and health promotion to better understand the later chapters on specific health problems. This new eleventh edition also features Next Generation NCLEX®-style case studies and questions, a new chapter covering all systems cancers, additional case studies within the nursing care plans, and updated and expanded evidence-based content throughout to best reflect the latest standards and trends impacting pediatric nursing care today."-- Provided by publisher
Perspectives of pediatric nursing -- Social, cultural, religious, and family influences on child health promotion -- Developmental and genetic influences on child health promotion -- Communication and physical assessment of the child and family -- Pain assessment and management in children -- Childhood communicable and infectious diseases -- Health promotion of the newborn and family -- Health problems of newborns -- Health promotion of the infant and family -- Health problems of infants -- Health promotion of the toddler and family -- Health promotion of the preschooler and family -- Health problems of toddlers and preschoolers -- Health promotion of the school-age child and family -- Health promotion of the adolescent and family -- Health problems of school-age children and adolescents -- Impact of chronic illness, disability, and end-of-life care on the child and family -- Impact of cognitive or sensory impairment on the child and family -- Family-centered care of the child during illness and hospitalization -- Pediatric nursing interventions and skills -- The child with respiratory dysfunction -- The child with gastrointestinal dysfunction -- The child with cardiovascular dysfunction -- The child with hematologic or immunologic dysfunction -- The child with cancer -- The child with genitourinary dysfunction -- The child with cerebral dysfunction -- The child with endocrine dysfunction -- The child with musculoskeletal or articular dysfunction -- The child with neuromuscular or muscular dysfunction -- The child with integumentary
Includes bibliographical references.
Keywords: PEDIATRIC NURSING